Suppression of Optical Rogue Waves by Dispersion Oscillating Fiber in the Mid-infrared Supercontinuum - Liu, Shuo; Han, Xin; lv, Jiaqi; Feng, Yanhui; Xia, Yuanqin; Bai, Zhenxu (Frontiers in Physics, 2021)
We further numerically study the mid-infrared supercontinuum (SC) and the rare optical rogue wave (ORW) generated by femtosecond pulse pumping in chalcogenide fibers. Specifically, it is shown via ensembles of numerical simulations that the compression of the spectrum by dispersion oscillating fiber (DOF) effectively controls the generation of ORW. A comparison is made between uniform fiber (UF) and DOF, the spectral bandwidth is compressed from 5,800 nm of UF to 2,300 nm of DOF, and the ORW of high peak power is suppressed. In addition, the oscillation amplitude, oscillation period and initial phase of DOF dispersion are further changed. It has been proved that the suppression effect of ORW is the best when the oscillation amplitude is 300 ps2/km, the oscillation period is 0.5 cm and the initial phase is 0. We believe that our research results will provide some enlightenment for controlling the direction of ORW by changing the characteristics of optical fiber, improving the performance of SC.